Gestión escolar de calidad para el desarrollo institucional, en la Unidad Educativa " Nuestra Señora de Pompeya" de Saquisilí. Diseño de una planificación estratégica. - Sandoval Chanco, Bertha Cecilia (2016)
This research deals with the design of an educational strategic planning in the Education Unit "Our Lady of Pompeii", is performed to detect deficiencies in managing both teaching and learning processes perceived by principals and teachers of the school at primary level and secondary, which have generated a problem constraints on institutional development and knowledge and thinking based on school quality, parallel problem constraints on institutional development and knowledge and thought. This is why it is considered important to analyze the object of study on the influence that the school management has in the local schools because through it is possible to find routes of action to fulfill educational goals better conditions, developing better learning. Being a graduate in Basic Education, my goal is to strengthen the institutional development through strategic planning to investigate the relationship between the characteristics of the management that takes place in the institution and its quality and help institutional development for both members the institution and all who make up the educational community. By using the deductive method where you work from the general to the particular, to draw conclusions and consequences leading to a school quality. This document is formed by four chapters. I chapter in the theoretical contextualization of the problem is shown; Chapter II methodology and structure of the research project; Chapter III contains: research results and Chapter IV contains: the proposal, which sets out formally